INTEGRASI PENDIDIKAN LALU LINTAS DI SEKOLAH - Aryani, Ine Kusuma (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2019)
Traffic and road transport have a strategic role to support national development and integration as part of efforts to promote public welfare as mandated by the 1945 Constitution of the Republic of Indonesia. As part of a transportation system that has to be developed its potential and role to create security, safety, discipline and smooth traffic and road transportation in order to support economic development and the development of science and technology, in Law number 22 of 2009 concerning traffic and road transportation, it is explicitly stated that there is a sharpening of the formulation of principles and objectives, which is in addition to creating traffic and road transportation that is safe, secure, discipline, smooth and integrated with other transportation models, the Law aims at supporting the national economy, realizing public welfare and national unity, and upholding the dignity of the nation. Therefore, aspects of security and safety are a concern in realizing ethics and cultures in a cross-disciplined manner, through efforts of guidance and education from an early age in elementary schools in a sustainable manner so that it is expected to reduce the number of traffic accidents which tend to be dominated by school age. One reason is due to the many violations and less knowledge of legal awareness in traffic. Ethics and cultural of traffic is implemented in the teaching and learning process that is integrated through 2013 curriculum since early age with techniques and methods of learning that are conducive and correct with teaching materials for elementary school so they understand traffic procedures that can benefit themselves and others, and in the end can realize security, safety, order and smooth traffic